Killing the rising sun [compact disc, unabridged] : how America vanquished World War II Japan - O'Reilly, Bill; Dugard, Martin (Macmillan Audio, 2016)
Autumn 1944. World War II is nearly over in Europe but is escalating in the Pacific, where American soldiers face an opponent who will go to any length to avoid defeat. The Japanese army follows the samurai code of Bushido, stipulating that surrender is a form of dishonor. Killing the Rising Sun takes listeners to the bloody tropical-island battlefields of Peleliu and Iwo Jima and to the embattled Philippines, where General Douglas MacArthur has made a triumphant return and is plotting a full-scale invasion of Japan.